Potential Systemic Risk Effects Of Credit Relaxation In The Financial Industry As The Effect The COVID-19 - Suwinto Johan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
The granting of credit relaxation has caused polemics in the early days of the spread of COVID-19 in Indonesia. As a result of the spread of COVID-19, several industrial sectors have experienced unworkable conditions. Companies in this industry are not able to pay off their financial obligations to the Banking or Financing Company. The government asked financial industry players to provide credit relaxation. This was conveyed by the government, however, without being included with fixed procedures and direct communication with business players. In addition to this relaxation, there is a systemic risk. This research is in the form of qualitative research. This research focuses on the effect of credit relaxation on the finance and banking industries. This research proposes that the government determines the overall policy. Businesses, finance companies, and banks focus on the implementation procedures controlled by the Financial Services Authority. The government needs to take a more aggressive and comprehensive policy towards relaxation policies so that this relaxation policy can be carried out correctly to support the economy of small and medium enterprises again. If this policy is not comprehensive, it is feared that it will create higher new risks to the financial sector and the national economy.